2020
DOI: 10.1109/jlt.2019.2960804
|View full text |Cite
|
Sign up to set email alerts
|

Silica Hollow-Core Negative Curvature Fibers Enable Ultrasensitive Mid-Infrared Absorption Spectroscopy

Abstract: Ultrasensitive mid-infrared absorption spectroscopy was demonstrated by the use of a novel silica-based hollow-core negative curvature fiber (HC-NCF). The HC-NCF used in this work consists of a single ring of six nontouching cladding capillaries around the hollow core, thus forming a unique core boundary with a negative curvature. Such a silica HC-NCF enables the broadband single-mode transmission in the mid-infrared. By using the HC-NCF as a compact gas cell, a proof-of-principle experiment was conducted to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Therefore, the application of the HCFs, especially the ARHCFs, seems to be a promising way to deliver low-volume, robust, and long optical paths. A successful demonstration of TDLAS-based gas sensors aided with ARHCFs has been already demonstrated by several research groups justifying the viability of this approach [21,24,35,38]. Nikodem et al reported in [21] a very simple carbon dioxide (CO 2 ) sensor configuration utilizing a silica-based 7 capillary ARHCF as depicted in Figure 3.…”
Section: Tunable Diode Laser Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the application of the HCFs, especially the ARHCFs, seems to be a promising way to deliver low-volume, robust, and long optical paths. A successful demonstration of TDLAS-based gas sensors aided with ARHCFs has been already demonstrated by several research groups justifying the viability of this approach [21,24,35,38]. Nikodem et al reported in [21] a very simple carbon dioxide (CO 2 ) sensor configuration utilizing a silica-based 7 capillary ARHCF as depicted in Figure 3.…”
Section: Tunable Diode Laser Absorption Spectroscopymentioning
confidence: 99%
“…The interaction leads to the absorption of light by the gas molecules, which are excited at the wavelength corresponding to the selected molecular transition. This phenomenon is governed by the Beer-Lambert law and expressed by the following formula [34,35]:…”
Section: Tunable Diode Laser Absorption Spectroscopymentioning
confidence: 99%
“…A piece of standard fiber was coiled around a piezo transducer (PZT) and was used to make sure that the interferometer operated at the quadrature point. In [73], the same group presented another system, operating at 3.6 µm. The fiber was 1.2-m-long, had a core diameter of 65 µm, and had a transmission band from 1.6 µm to the mid-infrared region.…”
Section: Trace-gas Detection Using Hollow-core Fibers With Inhibited mentioning
confidence: 99%
“…The sample absorption spectrum measured when the laser wavelength was scanned across the nitrous oxide transition near 2203.75 cm -1 is presented in Figure 14b. When the WMS technique was implemented, the detection limit of a few parts-per-billion was obtained and the response time was 23 s. In [73], the same group presented another system, operating at 3.6 µm. The fiber was 1.2-m-long, had a core diameter of 65 µm, and had a transmission band from 1.6 µm to the mid-infrared region.…”
Section: Trace-gas Detection Using Hollow-core Fibers With Inhibited mentioning
confidence: 99%
See 1 more Smart Citation